Investing in green business and sustainable development (Economics and region, 2024)
The article is devoted to the study of the role of investment in the development of green business as an important factor in the sustainable development of Ukraine's economy. The paper examines the essence of green business, which focuses on minimizing the negative impact on the environment through innovative solutions and environmentally friendly technologies. It is noted that investments in this sector contribute to the introduction of innovations, modernization of enterprises, reduction of harmful emissions and introduction of energy-efficient technologies, which forms the basis for a balance between economic growth, environmental sustainability and social justice. Particular attention is paid to the analysis of the Environmental Performance Index (EPI) for Ukraine, which allows to assess environmental efficiency and the role of investments in addressing environmental challenges. EPI's analysis showed that Ukraine's position in the country ranking is declining, which is indicative of environmental challenges that have been exacerbated by the Russian-Ukrainian war. The article also analyzes the Green Growth Index (GGI), which reflects the development of the green economy in the country, in particular, in terms of resource efficiency, protection of natural capital, development of green economic opportunities, and social integration. The GGI analysis shows stability and slight improvement, especially in the indicators of natural capital protection and development of green economic opportunities, which indicates the effectiveness of investments in green business. The development of the bioeconomy as a component of the green economy, which increases competitiveness in international markets, is separately considered. Financial instruments for investing in green business, including green bonds, investment funds, direct investment (venture capital), green loans, grants and subsidies, green insurance products, crowdfunding of environmental projects, and environmental stock indices are considered. The author concludes that investment in green business is a strategic tool for achieving sustainable development and improving Ukraine's environmental performance in the face of global challenges.
Keywords: investment; green business; green economy; sustainable development; economic competitiveness; bioeconomy